The Future of the Utility Field Area Network. Issue 12 (12th June 2019) - Timberg, Chris; Simovic, Uros
Abstract : Smart Grid devices and technologies are being deployed by utilities across the country to improve operational efficiency, reliability, security, and resilience. As utilities deploy increasingly more managed devices onto their transmission and distribution systems, there is an ever‐growing need for a more reliable, secure, and interoperable communication network. This is where the need for a robust communication system comes into play. The field area network (FAN) is arguably the most complex piece of the communications network, since it is primarily responsible for providing "last‐mile" communications to end‐devices. Until recently, FANs were deployed to serve a limited purpose—for example, only for distribution automation (DA) or substation automation (SA). Today, we must think beyond DA and SA. A more expansive use of the FAN, as it relates to other layers of utility telecommunications, is displayed inFigure 1 .